2017
DOI: 10.1111/apa.14086
|View full text |Cite
|
Sign up to set email alerts
|

Symptom management and psychological support for families are the cornerstones of end‐of‐life care for children with spinal muscular atrophy type 1

Abstract: Our study found that symptom management and psychological support for families were the cornerstones of end-of-life care for children with SMA1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 13 publications
0
9
0
6
Order By: Relevance
“…37 Further, information delivered to parents using medical jargon left parents distressed and requiring further clarification but often felt apprehensive to do so. 23,38,39…”
Section: Resultsmentioning
confidence: 99%
“…37 Further, information delivered to parents using medical jargon left parents distressed and requiring further clarification but often felt apprehensive to do so. 23,38,39…”
Section: Resultsmentioning
confidence: 99%
“…Morphine and benzodiazepines were used more (77%) over the last period than during the two previous ones studied in France (18 and 60%, respectively), but less than that in other studies when reported (8,22,23), and use of analgesics and/or sedative treatments has not been ruled yet in the last standards of care (5,10). However, pain and dyspnea were the main symptoms reported during the last 48 h in a recent retrospective study (22), underscoring the need to prioritize comfort for those infants. Of note, amitriptyline has also been used to ensure well-being and diminish anxiety due to chronic respiratory insufficiency but needs further evaluation.…”
Section: Discussionmentioning
confidence: 62%
“…2005-370, promulgated on April 22, 2005, and Law No. 2016-87 promulgated on February 2, 2016, regarding end of life and patients' right) has led to the implication of more home-hospital settings (26-62%) and involvement of dedicated pediatric palliative care teams (11-74%) in the management of those severe patients. If there was no evolution in NIV use over the period studied, oxygenotherapy, suction aspiration system, and enteral feeding through an NGT were used in most patients, as reported in other studies (8,15,22,23) and recommended in the recently revised consensus statement on standards of care in SMA (5,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations